Decoding of faces and face components in face-sensitive human visual cortex - Nichols, David F.; Betts, Lisa R.; Wilson, Hugh R. (Frontiers in Psychology, 2010)
A great challenge to the field of visual neuroscience is to understand how faces are encoded and represented within the human brain. Here we show evidence from functional magnetic resonance imaging (fMRI) for spatially distributed processing of the whole face and its components in face-sensitive human visual cortex. We used multi-class linear pattern classifiers constructed with a leave-one-scan-out verification procedure to discriminate brain activation patterns elicited by whole faces, the internal features alone, and the external head outline alone. Furthermore, our results suggest that whole faces are represented disproportionately in the fusiform cortex (FFA) whereas the building blocks of faces are represented disproportionately in occipitotemporal cortex (OFA). Faces and face components may therefore be organized with functional clustering within both the FFA and OFA, but with specialization for face components in the OFA and the whole face in the FFA.